THE IMPLEMENTATION OF DEMOCRACY TOWARD FREEDOM OF THE PRESS IN RUSSIA UNDER VLADIMIR PUTIN 2000-2008 - Ayunantari (2013)
This undergraduate thesis tries to explore the implementation of Democracy toward freedom of press as the civil liberties in Russia under Putin. During his administration in 2000 until 2008, he succeeded to solve the economical problem in Russia. Many reforms he made to increase the welfare of society after Yeltsin cannot give in his administration. He succeeded to raise the per capita income and erased the debt. He tried to bring Russia back into the power of world, except the economical factor